Selective inhibition of integrin αvβ6 leads to rapid induction of urinary bladder tumors in cynomolgus macaques. (14th December 2022) - Guffroy, Magali; Trela, Bruce; Kambara, Takahito; Stawski, Lukasz; Chen, Huidong; Luus, Lia; Montesinos, Monica S; Olson, Lauren; He, Yupeng; Maisonave, Kevin; Carr, Tracy; Lu, Min; et al.
Abstract: Administration of a novel and selective small molecule integrin αvβ6 inhibitor, MORF-627, to young cynomolgus monkeys for 28 days resulted in the rapid induction of epithelial proliferative changes in the urinary bladder of 2 animals, in the absence of test agent genotoxicity. Microscopic findings included suburothelial infiltration by irregular nests and/or trabeculae of epithelial cells, variable cytologic atypia, and high mitotic rate, without invasion into the tunica muscularis. Morphologic features and patterns of tumor growth were consistent with a diagnosis of early-stage invasive urothelial carcinoma. Ki67 immunohistochemistry demonstrated diffusely increased epithelial proliferation in the urinary bladder of several monkeys, including those with tumors, and αvβ6 was expressed in some epithelial tissues, including urinary bladder, in monkeys and humans. Spontaneous urothelial carcinomas are extremely unusual in young healthy monkeys, suggesting a direct link of the finding to the test agent. Inhibition of integrin αvβ6 is intended to locally and selectively block transforming growth factor beta (TGF-β) signaling, which is implicated in epithelial proliferative disorders. Subsequent in vitro studies using a panel of integrin αvβ6 inhibitors in human bladder epithelial cells replicated the increased urothelial proliferation observed in monkeys and was reversed through exogenous application of TGF-β. Moreover, analysis of in vivo models of liver and lung fibrosis revealed evidence of epithelial hyperplasia and cell cycle dysregulation in mice treated with integrin αvβ6 or TGF-β receptor I inhibitors. The cumulative evidence suggests a direct link between integrin αvβ6 inhibition and decreased TGF-β signaling in the local bladder environment, with implications for epithelial proliferation and carcinogenesis.